2006
DOI: 10.1002/jso.20566
|View full text |Cite
|
Sign up to set email alerts
|

Number of lymph node metastases and its prognostic significance in early gastric cancer: A multicenter italian study

Abstract: Nodal involvement confirmed to be a significant prognostic factor. In view of the trend to a lower risk of recurrence when more than 15 nodes were retrieved and the better staging achieved we consider D2 lymphadenectomy the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
96
2
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 31 publications
13
96
2
7
Order By: Relevance
“…Radical surgery with lymph node dissection has provided an excellent therapeutic outcome; the 5-year survival rate after curative resection is more than 90%, including fi ndings in recent European series [4,14,[16][17][18][19][20][21]. In Japan, analyses of databases containing a large number of pathology reports, patients' histories, and long-term survival data from major leading hospitals have demonstrated that the 5-year cancer-specifi c survival rates of EGC limited to the mucosa or the submucosa are 99% and 95%, respectively [4].…”
Section: Discussionmentioning
confidence: 99%
“…Radical surgery with lymph node dissection has provided an excellent therapeutic outcome; the 5-year survival rate after curative resection is more than 90%, including fi ndings in recent European series [4,14,[16][17][18][19][20][21]. In Japan, analyses of databases containing a large number of pathology reports, patients' histories, and long-term survival data from major leading hospitals have demonstrated that the 5-year cancer-specifi c survival rates of EGC limited to the mucosa or the submucosa are 99% and 95%, respectively [4].…”
Section: Discussionmentioning
confidence: 99%
“…In western countries, Roviello et al [12], in their multicenter retrospective study, confi rmed nodal involvement to be a signifi cant prognostic factor for early gastric cancer. In view of the trend to a lower risk of recurrence when more than 15 nodes were retrieved and the better staging achieved, they concluded that D2 lymphadenectomy was the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…EGC is defined as gastric cancer that invades no more deeply than the submucosa, irrespective of lymph node metastasis [33]. It has been reported that about 10-15% of patients with EGC have lymph node metastasis [1,34,35]. Precise prediction of lymph node metastasis status in EGC is a very important issue because ESD has become increasingly popular as a minimally invasive treatment for EGC [36].…”
Section: Discussionmentioning
confidence: 99%